2022
DOI: 10.1016/j.jpedsurg.2021.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for short-term complications graded by Clavien-Dindo after transanal endorectal pull-through in patients with Hirschsprung disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Concerning the neurodevelopment, the review of McCan et al shows that there is no consensus about the possible higher risk from receiving anesthesia at a younger age [29]. Regarding the functional postoperative outcomes, we do know that older age at time of endorectal pull-through is a risk factor for developing postoperative complications [30]. However, we do not know how age at surgery influences the functional postoperative outcomes, due to lacking consensus [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the neurodevelopment, the review of McCan et al shows that there is no consensus about the possible higher risk from receiving anesthesia at a younger age [29]. Regarding the functional postoperative outcomes, we do know that older age at time of endorectal pull-through is a risk factor for developing postoperative complications [30]. However, we do not know how age at surgery influences the functional postoperative outcomes, due to lacking consensus [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…After removal of 3134 duplicates, 12,401 articles were screened on title and abstract and 471 articles were subsequently screened on full text. Ten articles fulfilled all inclusion criteria and were included in this systematic review ( Figure 1 ) ( 20 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies discussed surgical and anesthetic risks of various abdominal laparoscopic surgeries in 1778 children aged <1 years. The results are presented in Table 2 ; Supplementary Tables 1 – 10 ( 20 29 ). The reported laparoscopic surgeries included transanal endorectal pull-through (TERPT) for Hirschsprung disease, pyloric stenosis repair/pyloromyotomy, gastrostomy, congenital megacolon, diaphragmatic hernia, malrotation and inguinal hernia repair.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Freedman-Weiss et al on 282 patients found that for appropriately selected patients with Hirschsprung disease, delaying pull-through until the second month of life is associated with lower total and postoperative stays without increased readmissions or complications [16]. However, in another study by Beltman, L., et al, multivariate analysis showed that older age at surgery (median 105 days) increases the risk of developing postoperative complications (OR = 1.00, 95% CI = 1.00-1.01, p = 0.041) [17].…”
Section: A) Agementioning
confidence: 99%